Early Detection of Occupational Noise-Induced Hearing Loss in Dentists: A Cross-Sectional Study: Occupational Noise-Induced Hearing Loss in Dentists - Ghasemi, Hadi; Mirmohammadi, Seyyed Jalil; Ebn Ahmadi, Arezoo; Tabatabaei, Atefe-alsadat (Journal of Dental School, 2025)
Objective(s): Noise-induced hearing loss (NIHL) is a critical occupational hazard, particularly among dentists exposed to high-frequency sounds from dental equipment. This study aimed to assess hearing thresholds in dentists using Pure Tone Audiometry (PTA) and High-Frequency Audiometry (HFA). Methods: A cross-sectional study was conducted with 63 dentists in Yazd, Iran, who underwent audiometric testing across frequencies ranging from 250 Hz to 16,000 Hz. Dentists over 50 years old and those with a history of hearing problems or ototoxic drug use were excluded. Statistical evaluation included independent t-tests, ANOVA, Pearson’s correlation coefficient, and Chi-square tests at a significance level of 0.05. Results: hearing loss was most prevalent at 4,000 Hz in the normal frequency range, affecting 35% of participants in the right ear and 33% in the left ear. High-frequency hearing loss was significantly higher, with 86% of dentists exhibiting hearing loss at 16,000 Hz in the right ear and 79% in the left ear. The study also found a significant correlation between hearing thresholds, age, and work experience, emphasizing the increased risk of NIHL with prolonged exposure to dental equipment noise. Gender differences were noted, with men showing higher rates of hearing loss at 4,000 Hz. Conclusion: These findings underscore the necessity for regular auditory screening and the implementation of protective measures in dental practice to prevent long-term hearing damage. The study highlights the utility of HFA for early detection of NIHL, especially in high-risk professions like dentistry.